Становлення та особливості розвитку світових культур - Захаров, О. О. (ХНУРЕ, 2020)
The genesis of culture is quite complex and linked to the historical development of society. At the same time, cultural knowledge is also quite specific, affecting many areas of social development. However, without cultural knowledge it is impossible to speak of a civilized person, a society, the unthinkable progress of the future humanity
Keywords: культурне розмаїття; українознавство